2020
DOI: 10.1152/ajpheart.00019.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of blood pressure is altered following isolated leg heating in aged humans

Abstract: There is a sustained reduction in arterial blood pressure that occurs in aged adults following exposure to acute leg heating. However, the neurovascular mechanisms mediating this response remain unknown. Our findings demonstrate for the first time that this reduction in arterial blood pressure is mediated, in part, by a sympathoinhibitory effect that alters the compensatory neural response to hypotension in aged adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
(67 reference statements)
2
14
1
Order By: Relevance
“…However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ). Previous studies have alluded to the possibility that a certain threshold of hyperthermic intensity—such that can initiate profound increases in core temperature and/or alterations in sympathetic activity—may be required to elicit reductions in arterial stiffness and associated increases in distensibility (Caldwell et al, 2017 ; Kaldur et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ). Previous studies have alluded to the possibility that a certain threshold of hyperthermic intensity—such that can initiate profound increases in core temperature and/or alterations in sympathetic activity—may be required to elicit reductions in arterial stiffness and associated increases in distensibility (Caldwell et al, 2017 ; Kaldur et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…These reductions in BP occurred despite the absence of appreciable changes in intestinal temperature, thus implying that elevations in core body temperature are not a prerequisite for the hypotensive effects of HT in PAD patients. The mechanisms by which HT lowers BP remains poorly defined, but emerging evidence suggests that, in contrast to Plasma IL-6 (pg/mL) Treatment: p = 0.55 Time: p<0.01 Interaction: p = 0.30 c young individuals, aged adults do not display the characteristic increase in muscle sympathetic nerve activity following leg heating (Engelland et al, 2020). It has thus been proposed that a blunted neural compensatory response to HT-induced increases in leg vascular conductance partly underlies the hypotensive effects observed in elderly individuals (Engelland et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These reductions in BP occurred despite the absence of appreciable changes in intestinal temperature, thus implying that elevations in core body temperature are not a prerequisite for the hypotensive effects of HT in PAD patients. The mechanisms by which HT lowers BP remains poorly defined, but emerging evidence suggests that, in contrast to young individuals, aged adults do not display the characteristic increase in muscle sympathetic nerve activity following leg heating (Engelland et al., 2020). It has thus been proposed that a blunted neural compensatory response to HT‐induced increases in leg vascular conductance partly underlies the hypotensive effects observed in elderly individuals (Engelland et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism/s mediating the sustained increase in systemic vascular conductance and reduction in arterial blood pressure after acute heat exposure are yet to be fully elucidated. We recently utilized the microneurography technique to directly measure sympathetic nerve traffic in young and aged adults before and in recovery from acute leg heating (19). We found that the reduction in arterial blood pressure that occurs in aged adults 30 min after acute leg heating is mediated, in part, by a sympathoinhibitory effect that alters the compensatory neural response to hypotension.…”
Section: Cardiovascular Adjustments In Recovery From Acute Heat Exposurementioning
confidence: 99%